MULTI-OBJECTIVE OPTIMIZATION MODEL FOR A MULTI-DEPOT MIXED FLEET ELECTRIC VEHICLE SCHEDULING PROBLEM WITH REAL-WORLD CONSTRAINTS - DUDA, Jerzy; KARKULA, Marek; PUKA, Radosław; SKALNA, Iwona; FIEREK, Szymon; REDMER, Adam; KISIELEWSKI, Piotr (Problemy Transportu, 2022)
This paper presents the problem of public transport planning in terms of the optimal use of the available fleet of vehicles and reductions in operational costs and environmental impact. The research takes into account the large fleet of vehicles of various types that are typically found in large cities, including the increasingly widely used electric buses, many depots, and numerous limitations of urban public transport. The mathematical multi-criteria mathematical model formulated in this work considers many important criteria, including technical, economic, and environmental criteria. The preliminary results of the Mixed Integer Linear Programming solver for the proposed model on both theoretical data and real data from urban public transport show the possibility of the practical application of this solver to the transport problems of medium-sized cities with up to two depots, a heterogeneous fleet of vehicles, and up to about 1500 daily timetable trips. Further research directions have been formulated with regard to larger transport systems and new dedicated heuristic algorithms.